Aminophylline Partially Prevents the Decrease of Body Temperature during Laparoscopic Abdominal Surgery - Kim, Dae Woo; Lee, Jung Ah; Jung, Hong Soo; Joo, Jin Deok; In, Jang Hyeok; Jeon, Yeon Soo; Chun, Ga Young; Choi, Jin Woo (Journal of Korean medical science, 2014)
Aminophylline can elicit thermogenesis in rats or increase metabolic rate during cold stress in lambs. We tested the hypothesis that aminophylline would reduce the change in core body temperature during laparoscopic abdominal surgery requiring pneumoperitoneum. Fifty patients were randomly divided into an aminophylline group (n=25) and a saline control group (n=25). Esophageal temperature, index finger temperature, and hemodynamic variables, such as mean blood pressure and heart rate, were measured every 15 min during sevoflurane anesthesia. In the aminophylline group, esophageal temperatures at T45 (36.1±0.38 vs. 35.7±0.29, P=0.024), T60 (36.0±0.39 vs. 35.6±0.28, P=0.053), T75 (35.9±0.34 vs. 35.5±0.28, P=0.025), T90 (35.8±0.35 vs. 35.3±0.33, P=0.011), and T105 (35.8±0.36 vs. 35.1±0.53, P=0.017) and index finger temperatures at T15 (35.8±0.46 vs. 34.9±0.33, P<0.001), T30 (35.7±0.36 vs. 35.0±0.58, P=0.029), T45 (35.8±0.34 vs. 35.2±0.42, P=0.020), T60 (35.7±0.33 vs. 34.9±0.47, P=0.010), T75 (35.6±0.36 vs. 34.8±0.67, P=0.028), T90 (35.4±0.55 vs. 34.4±0.89, P=0.042), and T105 (34.9±0.53 vs. 33.9±0.85, P=0.024) were significantly higher than in the saline control group. Aminophylline is effective in maintaining the core temperature through a thermogenic effect, despite reduced peripheral thermoregulatory vasoconstriction.